Role of Sports in the Development of Motivation as a Psychological Parameter among the Students - Manzoor Khan; Alamgir Khan; Muhammad Zafar Iqbal Butt (Recent Trends in Sports, 2025)
This research study aimed to assess the role of sports in the development of motivation as a psychological parameter among students. The study's population consisted of both male and female physical education students enrolled in all universities, both public and private universities. KP, Pakistan. Two hundred twenty-six (226) students as a sample of the study. Under the direction of the study supervisor, the researcher created a Likert-type scale with five options that included 21 items in order to gather the necessary data. The researcher personally contacted every respondent during the collection of data. A self-made questionnaire with pertinent questions was created by the researcher for data collection, and the researcher personally distributed the questionnaires to the respondents and collected them once they had been completed. The appropriate statistical tools were used in accordance with parametric data after the gathered data was processed using statistical software for social sciences (SPSS, Version 24). Based on data analysis and findings, the researcher concluded that sports are a universal tool which promotes motivation among students. Likewise, the study also concluded that sports participation helps the students to have good motivation toward their goals, and healthy lifestyle activities such balanced diet, exercise, hygienic practices and disciplined behaviors.
Keywords: Healthy lifestyle; Sports; motivation; physical education students; psychological parameter